Handbook of sustainability research / edited by Walter Leal Filho - Filho, Walter Leal (ed.) (New York, 2005)
This handbook introduces concepts, ideas and methods of sustainability research based on real examples. It is divided into four sections. One part deals with theoretical aspects of sustainability and refers to theoretical approaches to sustainability research. Another section elaborates on more practical approaches to sustainability research, offering views and per spectives from various researchers, illustrating how regulations, laws and political frame works influence sustainability. A third part treats education for sustainability and presents research and practical projects, showcasing how sustainability research may focus in formal and non-formal education. The final section draws some conclusions based on the body of experiences and knowledge gathered by the authors. This handbook will be of great use to educators, scientists, researchers, politicians, environment activists, teachers and others interested in sustainability and in the implementation of results of sustainability research.
Keywords: Environmental socialization